MUTUAL LEGAL ASSISTANCE IN CIVIL PROCEEDINGS - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The principle of mutual legal assistance is a traditional one. It is governed by law, bilateral treaties as well as international conventions. Legal assistance is mutually offered by the courts, domestically and abroad. Therefore, we speak of domestic and international legal assistance. The legal assistance is provided in such a manner that a court undertakes actions in civil proceedings that are ongoing before another court. The most common form of legal assistance is to hear evidence in a situation when such evidence cannot be presented before the court conducting the civil proceedings. However the scope of the mutual legal assistance is much wider. It can be both necessary and expedient. The expediency of the legal assistance is more closely related to a situation when a domestic court is engaged to undertake a certain action in civil proceedings, while the expediency is the most evident when the legal assistance is requested by a foreign court or state organ. Application of the rules on the regulation of mutual legal assistance makes for more efficient civil proceedings, however it represents a deviation from the principle of direct, or immediate examination of evidence by the court conducting the proceedings.